До питання про вторинне цвітіння видів Cornaceae (Dumort.) Dumort. в Україні - Kustovskaya, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The literature sources, dedicated to the study of the phenomenon of the plant second flowering in the temperate zone have been analyzed. Peculiarities of dogwood family (Cornaceae (Dumort.) Dumort.) second flowering in Ukraine and the causes of this phenomenon have been considered.